Scientific Conceptual Understanding in Physics through Momentum and Material-Dependent Collisions Using the Dual Situated Learning Model: A Mixed Methods Action Research Study - Chorphaka Kromkhan; Kanyarat Cojorn; Chaweewan Seesom (Bumi Publikasi Nusantara, 2026)
From a materials science perspective, collision behavior depends on mass, velocity, and the mechanical responses of interacting materials, including elasticity, deformation, damping, and energy dissipation. This mixed-methods classroom action research examined the effectiveness of the Dual Situated Learning Model (DSLM) in improving students’ conceptual understanding of momentum and material-dependent collisions. Thirty-nine Grade 10 students from a secondary school in Thailand participated in three instructional cycles. Quantitative data were obtained from prerequisite and cycle-specific conceptual assessments, while qualitative data included worksheets, classroom observations, interviews, and reflection records. The results showed significant improvement in conceptual understanding, representational competence, and confidence in scientific explanations. Material-dependent collision contexts helped students distinguish momentum conservation from kinetic-energy dissipation and supported meaningful conceptual reconstruction in physics learning.